The Pre-Modern Manuscript Trade and its Consequences, ca. 1890–1945 (Arc Humanities Press, 2024)
This collection brings together current research into the development of the market for pre-modern manuscripts. Between 1890 and 1945 thousands of manuscripts made in Europe before 1600 appeared on the market. Many entered the collections in which they have remained, shaping where and how we encounter the books today. These collections included libraries that bear their founders’ names, as well as national and regional public libraries. The choices of the super-rich shaped their collections and determined what was available to those with fewer resources. In addition, wealthy collectors sponsored scholarship on their manuscripts and participated in exhibitions, raising the profile of some books. This volume examines the collectors, dealers, and scholars who engaged with pre-modern books, and the cultural context of the manuscript trade in this era.